Diffusible factors regulate hair cell regeneration in the avian inner ear. - Tsue, T T (1994)
Damage to the avian inner ear results in up-regulation of mitotic activity resulting in regeneration of hair cells. The objective of this investigation was to determine whether the damaged inner ear epithelium releases a soluble mitogen that is responsible for the up-regulation of proliferation. The sensory epithelium from normal and drug-damaged avian inner ears was cultured alone or in the presence of other cultures. As previously shown in vivo and in vitro, damaged organs displayed increased supporting cell proliferation compared with undamaged organs, leading to eventual morphologic and functional recovery. When damaged organs were cocultured with an undamaged organ, proliferation was increased in the undamaged tissue. When undamaged organs were cultured together, proliferation was decreased. These results indicate that a soluble factor released from the damaged inner ear epithelium stimulates proliferation and suggest the release of a factor from normal tissue that suppressed mitotic activity. Thus, reparative hair cell regeneration in the inner ear appears to be regulated by a balance between proliferative and antiproliferative paracrine factors.